Biogeochemical modelling of Ria Formosa : South Portugal - P. Duarte (2008)
Ria Formosa is a large (c.a. 100 km2) mesotidal lagunary system with large intertidal areas and several conflicting uses, such as fisheries, aquaculture, tourism and nature conservation. Its watersheds cover an area of approximately 864 km2, with a perimeter of 166 km and a maximum altitude of 522 m. There are about 100 different land use classes being divided among six major groups: 1) urban, 2) agricultural, 3) forest, 4) rangeland and pastures, 5) wetlands and 6) water bodies. The Soil and Water Assessment Tool (SWAT model) has been applied to the catchment areas in order to simulate water discharges to Ria Formosa providing forcing to a two-dimensional vertically integrated coupled physical-biogeochemical model, implemented with EcoDynamo - an object oriented modelling software. This model includes water column and sediment processes as well as their interactions and several biological sub-models (e.g. phytoplankton dynamics and bivalve growth). The main objectives of this work are to: (i) Evaluate the relative importance of land drainage, waste water treatment (WTP) plants and water exchanges, across the lagoon inlets, for nutrient dynamics; (ii) Analyse management scenarios related to changes in lagoon bathymetry and their potential effects on system dynamics. The obtained results are being used by the Ria Formosa Natural Park authority for management purposes and may be useful to feedback future updates of the watershed management plans, within the scope of the European Union Water Framework Directive.